The power of magnesium: unlocking the potential for increased yield, quality, and stress tolerance of horticultural crops - Ahmed, Nazir; Zhang, Baige; Bozdar, Bilquees; Chachar, Sadaruddin; Rai, Mehtab; Li, Juan; Li, Yongquan; Hayat, Faisal; Chachar, Zaid; Tu, Panfeng (Frontiers in Plant Science, 2023)
Magnesium (Mg2+) is pivotal for the vitality, yield, and quality of horticultural crops. Central to plant physiology, Mg2+ powers photosynthesis as an integral component of chlorophyll, bolstering growth and biomass accumulation. Beyond basic growth, it critically affects crop quality factors, from chlorophyll synthesis to taste, texture, and shelf life. However, Mg2 + deficiency can cripple yields and impede plant development. Magnesium Transporters (MGTs) orchestrate Mg2+ dynamics, with notable variations observed in horticultural species such as Cucumis sativus, Citrullus lanatus, and Citrus sinensis. Furthermore, Mg2+ is key in fortifying plants against environmental stressors and diseases by reinforcing cell walls and spurring the synthesis of defense substances. A burgeoning area of research is the application of magnesium oxide nanoparticles (MgO-NPs), which, owing to their nanoscale size and high reactivity, optimize nutrient uptake, and enhance plant growth and stress resilience. Concurrently, modern breeding techniques provide insights into Mg2+ dynamics to develop crops with improved Mg2+ efficiency and resilience to deficiency. Effective Mg2+ management through soil tests, balanced fertilization, and pH adjustments holds promise for maximizing crop health, productivity, and sustainability. This review unravels the nuanced intricacies of Mg2+ in plant physiology and genetics, and its interplay with external factors, serving as a cornerstone for those keen on harnessing its potential for horticultural excellence.